The effect of service quality and customer perceived value on customer satisfaction with trust as a mediating variable - Griseldis, Kelvin; Andi Mesta, Hendri (Marketing Management Studies, 2024)
The purpose of this study was to analyze: (1) The effect of Service Quality on ANS Bus Customer Satisfaction in Padang City (2) The Effect of Customer Perceived Value on ANS Bus Customer Satisfaction in Padang City (3) The Effect of Service Quality on Trust ANS Buses in Padang City (4) Effect of Customer Perceived Value on ANS Bus Trust in Padang City (5) Effect of Trust on ANS Bus Customer Satisfaction in Padang City (6) Effect of Service Quality on ANS Bus Customer Satisfaction in Padang City with Trust as a mediating variable (7) Effect of Customer Perceived Value on ANS Bus Customer Satisfaction in Padang City with Trust as a mediating variable. The results of the study are (1) The effect of Service Quality has a significant effect on ANS Bus Customer Satisfaction in Padang City (2) The Effect of Customer Perceived Value has a significant effect on ANS Bus Customer Satisfaction in Padang City (3) The Effect of Service Quality has a significant effect on Trust Bus ANS in Padang City ( 4) The effect of Customer Perceived Value has a significant effect on ANS Bus Trust in Padang City (5) The effect of Trust has a significant effect on ANS Bus Customer Satisfaction in Padang City (6) The effect of Service Quality has a significant effect on ANS Bus Customer Satisfaction in Padang City with Trust as a mediating variable ( 7) ) The effect of Customer Perceived Value has a significant effect on ANS Bus Customer Satisfaction in the City of Padang with Trust as a mediating variable.